Groundwater and the water-food-energy nexus: The grants for water resources use and its importance and necessity of integrated management - Moraes-Santos, Eliana Cristina [UNESP] (2021)
According to the Brazilian National Water Resources Policy, water is a limited public good, and its management involves the participation of public authorities, users, and communities. This paper analyzes data on groundwater concession and uses in five Brazilian municipalities, located in the northeastern region of the Paraiba do Sul River Basin. Data were analyzed to associate aquifer systems and groundwater use with electricity consumption of the water supply systems and food production, in the perspective of the water-food-energy nexus. This analysis aimed to quantify the exploited water flows and if it is adequate with the capacity of the aquifers. For data analysis and interpretation, statistical techniques were used, which allowed structuring, organizing, and associating the information. The results indicate that, among the regional aquifer systems, the Cacapava System is the most explored in terms of groundwater abstraction, with an average of 9769 m(3)/h, of which only 1331 m(3)/h is used for public supply and 8456 m(3)/h for private use. One finding of this research was to verify that just one of the municipalities studied makes public the use of groundwater abstraction, with consequences in public policy and alerting to the need for adequate inspection in the areas of underground well-drilling for non-contamination and better maintenance of aquifer systems. The results highlight the water-food-energy nexus in the study area, indicating that municipalities with large rice cultivation areas use or store most of the water resources for agricultural use. Promoting new sustainable actions and achieving the Sustainable Development Goals requires integrated management outside the traditional sectors and water-food-energy nexus approach.